Sago palm (Metroxylon spp.) is a tropical plant adapted to marginal land such as fresh water swamp, peat swamp or brackish water. The objective of the researche is to identify physical and chemical habitat characteristics of sago palm in the Seram island, Maluku. The research was conducted in nine months from March to November 2009. The observation was conducted at three samples area, namely Luhu (West Seram District), Sawai (Central Maluku District), and Werinama (East Seram District). Soi - Samin Botanri; Dede Setiadi; Edi Guhardja; Ibnul Qayim; Lilik B. Prasetyo (Forum Pasca Sarjana, 2011)
Sago palm (Metroxylon spp.) is a tropical plant adapted to marginal land such as fresh water swamp, peat swamp or brackish water.  The objective of the researche is to identify physical and chemical habitat characteristics of sago palm in the Seram island, Maluku.  The research was conducted in nine months from March to November 2009.  The observation was conducted at three samples area, namely Luhu (West Seram District), Sawai (Central Maluku District), and Werinama (East Seram  District).  Soil and water samples were taken at samples area and analyzed at Soil Research Center Laboratory, Bogor.  Result showed that sago palm at the Seram island can be found at four different habitat types, namely: 1) upland habitat/dry land, 2) temporary inundated fresh water swamp, 3) temporary inundated brackish water, and 4) permanent inundated fresh water swamp.  Soil texture of these habitats characterized by clay-loam and silty-clay with average bulk density of about 1.20.  The soil has acidic reaction that consists of medium soil organic and having medium cation exchange capacity (CEC).  Except for Fe and Alwhich were high, the nutrient content of the soil was very low. Salinity of water was less than 1.0 ppt (part per thousand).  Nitrate (NO3-), phosphate (PO43-) and other cation such us NH4+, K+, Ca2+, and Mg2+ were found relatively high in water.  Micro climate condition under sago stands (clump of Sago) such us temperature, relative humidity, and sun radiation intensity are low with very narrow fluctuation.  Micro-climate conditions were characterized by temperature ranging from 22,69oC to 23,94oC, meanwhile relative humidity ranging from 87,97 to 91,60%.  In case of  sun light intensity at near clump of sago palm reached of about 206,53 lux (12,40%).   Keywords: habitat type, Metroxylon spp., land, micro climate, Seram Island